2018
DOI: 10.18203/2394-6040.ijcmph20182648
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of burn injury among patients admitted in a Tertiary Care Hospital of Jharkhand

Abstract: Background: Burn despite being easily preventable is a critical health problem worldwide. With effective managements there is decline in burn cases in developed countries but trend is still rising in developing countries like India. This study was conducted to know the socio-demographic profile and pattern of burn injury in patients admitted in burn unit of tertiary care hospital.Methods: A hospital based cross sectional study was conducted for a period of six months using semi-structured questionnaire for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
4
8
0
Order By: Relevance
“…In the present study, males were twice more affected than females, findings which were in agreement with reports from other studies [7,14] but contrary to those from India [4,15]. The reason for the male preponderance could be explained by the behavior of this study population, which is characterized by a marked ability to explore the environment, excessive motor activity, and less carefulness [13].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, males were twice more affected than females, findings which were in agreement with reports from other studies [7,14] but contrary to those from India [4,15]. The reason for the male preponderance could be explained by the behavior of this study population, which is characterized by a marked ability to explore the environment, excessive motor activity, and less carefulness [13].…”
Section: Discussionsupporting
confidence: 92%
“…A substantial number of patients sustained burn injuries at home, similar to findings from elsewhere [3,4,15]. This study found out that most of the burn injuries occurred during late morning and evening hours similar to what was reported in another study [17].…”
Section: Causes Of Burn Injurysupporting
confidence: 90%
See 2 more Smart Citations
“…The study sample included 180 patients. This sample was deemed sufficient by using an Open-epi calculator to achieve a 95% confidence interval and a corresponding 5% margin of error, where the proportion of lower limb burn injuries was set to 8.9% ( Kumar et al, 2018 ). The criteria of inclusion in this study included adult patients of both genders living in the KSA who presented themselves to the emergency department of the King Khalid Hospital and Prince Sultan Center for Health Services or Prince Sattam Bin Abdulaziz University hospital in Al Kharj between October 2018 and October 2019 with at least one documented burn injury prior to admission to the hospital.…”
Section: Methodsmentioning
confidence: 99%